DC fault ride-through capability and STATCOM operation of a HVDC hybrid voltage source converter - Feldman, Ralph; Farr, Ewan; Watson, Alan James; Clare, Jon C.; Wheeler, Patrick (IET, 2014)
HVDC transmission systems are becoming increasingly popular when compared to conventional AC transmission methods. HVDC voltage source converters (VSC) can offer advantages over traditional HVDC current source converter topologies; as such, it is expected that HVDC-VSCs will be further exploited with the growth of HVDC transmission. This paper presents the DC fault ride through capability and new STATCOM modes of operation for the recently published Alternate Arm Converter (AAC), intended for the HVDC market. Operation and fault ride through of the converter during a local terminal to terminal short circuit of the DC-Link is demonstrated; during the fault STATCOM operation is also demonstrated.